Volume guarantee ventilator of newborn - Anucha Thatrimontrichai; Waricha Janjindamai (Journal of Health Science and Medical Research (JHSMR), 2010)
The pathogenesis of bronchopulmonary dysplasia (BPD) is multifactorial. One cause is ventilatorinduced lung injury (VILI). Experimental studies show that the magnitude of volutrauma is more closely associated with ventilator-induced lung injury rather than end-inspiratory pressure. The volume guarantee (VG) mode, studied most thoroughly, provides automatic weaning of peak pressure in response to improving lung compliance and respiratory effort. A more consistent tidal volume, fewer excessively large breaths, lower peak pressure, less hypocarbia and lower levels of inflammatory cytokines have been documented. These short-term benefits translate into a shorter duration of ventilation.